PERANCANGAN IDENTITAS VISUAL SIRUP KAYU MANIS “ALFAFA” KABUPATEN KERINCI - BENNY WIJAYA SATRIA, Eliya Pebriyeni, S.Pd., M.Sn., San Ahdi, S.Sn., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Alfafa is one of the businesses that produce quality cinnamon beverage drinks, which has been producing large amounts of syrup along with the many market demands. Established in 2005 based on TDI No : 888/.I/Indag/2005 and health service number P-IRT: 113150103024. Establish this business becausein the district of Kerinci is one of the largest cinnamon bark suppliers in Indonesia. With the aim of advancing the regional economy of Kerinci district.The purpose of designing Identity Visual Sweetwood Syrup of Kerinci Alfafa Regency is to create a new Visual Identity of Alfafa Cinnamon Sauce without losing its old shape, and also consideration of weaknesses, opportunities and threats hat compare to the packaging and brands of Alfafa Sweet Syrup with competitors.the design method begins with data collection, observation, interviews and documentation so that problems that occur in the promotion of Alfafa Cinnamon Syrup can be known, from the identification of the problem, by conducting SWOT analysis.The design produces the main media in the form of packaging that is packed in the form of thick paperboard with desplaying visualization and information from Alfafa Cinnamon Syrup. Supporting media used in design of visual Identity of Sweet Syrup of Regency of Kerinci Alfafa among others, poster, business card, X-banner, pin, totebag, stamp, T-shirt, bottle label.Keywords: Designing, Promotion, Cinnamon, Packaging